Sosialisasi Manajemen Pemasaran Berbasis Online Untuk Pelaku UMKM di Kelurahan Jombang Kecamatan Cputat Tangerang Selatan - Tohiroh Tohiroh; Adhy Firdaus; Joned C Saksana; Fajar Sasongko; Siti Mulasih; Sutaryono Sutaryono; Sukardi Sukardi; Patria Adiguna; Asep Surya Lesmana; Melati Puspita Hakim; Idrisi Raliya Putera; Delima Indah; Rismayanti Rismayanti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The purpose of this activity is to assist Small and Micro Enterprises (SMEs) in understanding and implementing online-based marketing strategies to increase their product sales. The target of this activity is SMEs operating in Kelurahan Jombang, most of whom are members of the local Posyandu. This activity was conducted in April 2021 and included several educational sessions and hands-on practices on using social media and e-commerce platforms for product marketing. The results of this activity showed an improvement in the participants' understanding and skills in managing online marketing. The participants became more familiar with digital marketing techniques, such as creating engaging content, using social media, and optimizing e-commerce platforms. The implications of this activity are very positive, as SMEs have begun to adopt online marketing in their daily operations. This is expected to increase market reach, expand the customer base, and ultimately boost their sales and income. Furthermore, this activity also strengthens collaboration among SMEs and encourages entrepreneurial spirit within the local community.